Experiences of quality of life the first year after stroke in Denmark and Norway. A qualitative analysis - Pedersen, Synne Garder; Anke, Audny; Aadal, Lena; Pallesen, Hanne; Moe, Siri; Arntzen, Cathrine (International Journal of Qualitative Studies on Health and Well-being, 2019)
Purpose : This study aims to explore quality of life (QOL) during the first year of recovery after stroke in North Norway and Central Denmark. Method : Individual in-depth interviews with 11 stroke survivors were performed twelve months after stroke onset. An interpretative, inductive approach shaped the interview process and the processing of data. Results : We found that QOL reflected the individuals’ reconstruction of the embodied self, which was identified by three intertwined and negotiating processes: a familiar self, an unfamiliar self, and a recovery of self. Further, we found that reconstruction of the embodied self and QOL could be framed as an ongoing and interrelated process of “ being, doing, belonging and becoming ”. Enriching social relations, successful return to work, and continuity and presence in professional support during recovery enhanced the experience of QOL. Fatigue and sustained reduced function hindered participation in meaningful activities and influenced the perceived QOL negatively. Conclusions : The two countries differed in descriptions of continuity and support in the professional follow-up during the recovery process, influencing the degree of encouragement in reconstructing the embodied self. Reconstruction of the embodied self is a means of understanding stroke survivors’ QOL during the first year of recovery, supporting an individualized and tailored rehabilitation practice.